Parameter estimation based robust liquid level control of quadruple tank system — Second order sliding mode approach. (August 2021) - Gurjar, Bhagyashri; Chaudhari, Vinita; Kurode, Shailaja
Abstract: This article proposes a liquid level control scheme for a quadruple tank process (QTP) plant. A robust control is proposed using higher order sliding mode (HOSM) control. The four tank setup has opposite tanks actuated by a single pump and unmeasured liquid outflow from upper tanks affecting the levels in the lower tanks. This renders nonlinearity in the dynamics with uncertain behavior. A novel experimentation based estimator is proposed for identification of the unknown control valve ratios of the plant. The estimated parameter is used for robust control design and state observer model. The unmeasurable states are estimated using a sliding mode observer and the required derivatives of liquid levels in the tanks are evaluated using a HOSM differentiator. The complete schema is tested in simulation and validated experimentally on a QTP setup. Highlights: Parameter and state estimation based robust control of a cross coupled QTP. Higher order sliding mode (HOSM) control for robust performance. Sliding mode observer based state estimation. Proposal of a novel parameter estimator using HOSM differentiator. Experimentation based validation on a laboratory setup.